Expression of Met/hepatocyte growth factor receptor gene and malignant behavior of musculoskeletal tumors. - Scotlandi, K. (1996)
Overexpression of the hepatocyte growth factor receptor (Met/HGF receptor), a transmembrane tyrosine kinase encoded by the met proto-oncogene, has been associated with tumor progression in different human carcinomas. More recently, the Met/HGF receptor has also been described in tumor cell lines of mesenchymal origin, suggesting the existence of an autocrine loop that may contribute to the pathogenesis of sarcomas. In this study, we analyzed the expression of Met/HGF receptor by Western blotting and immunohistochemistry in frozen samples of 87 primary tumors of bone and soft tissues. Among benign tumors, overexpression was consistently found only in giant-cell tumor, a locally aggressive lesion that may also, although rarely, spread to the lung. Among malignant lesions, the presence of the Met/HGF receptor was detected in a relevant percentage of primaries and in almost all of the recurrences. The highest levels of Met/HGF receptor were found in osteosarcoma, a highly aggressive tumor that typically permeates the host bone and rapidly expands to the soft tissues. On the contrary, only low levels of Met/HGF receptor were found in chondrosarcoma, a slowly growing tumor that usually expands without massive destruction of the surrounding structures. These data indicate an association of Met/HGF expression with local aggressiveness in human mesenchymal tumors. The finding of Met/HGF receptor overexpression in all of the osteosarcomas suggests a role for the met proto-oncogene in the pathogenesis of this tumor.